2016
DOI: 10.5194/adgeo-42-1-2016
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation response to El Niño/La Niña events in Southern South America – emphasis in regional drought occurrences

Abstract: Abstract. The ENSO phenomenon is one of the key factors that influence the interannual variability of precipitation over Southern South America. The aim of this study is to identify the regional response of precipitation to El Niño/La Niña events, with emphasis in drought conditions. The standardized precipitation index (SPI) was used to characterize precipitation variabilities through the 1961-2008 period for time scales of 3 (SPI3) and 12 (SPI12) months. A regionalization based on rotated principal component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 54 publications
0
37
1
7
Order By: Relevance
“…Three drought categories were used for hydrological drought assessment, based on the categories established for the SPI to define meteorological drought conditions [36]. Table 2 shows the SSI categories, which are in line with recent research based on the SSI [31,32,37,38] and will help to compare the results obtained considering meteorological drought assessment based on the SPI over SSA (e.g., [39]). …”
Section: Methodsmentioning
confidence: 55%
“…Three drought categories were used for hydrological drought assessment, based on the categories established for the SPI to define meteorological drought conditions [36]. Table 2 shows the SSI categories, which are in line with recent research based on the SSI [31,32,37,38] and will help to compare the results obtained considering meteorological drought assessment based on the SPI over SSA (e.g., [39]). …”
Section: Methodsmentioning
confidence: 55%
“…In the southern region of Brazil, El Niño events cause increased precipitation and higher temperatures. In contrast, intense La Niña events can produce severe droughts (Grimm and Tedeschi, 2009; Abelen et al, 2015; Penalba and Rivera, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…de Oliveira‐Júnior et al () studied the relationship of SPI and ENSO/PDO for 14 rainfall stations in Brazil and detected indirect relationships of oscillations on the occurrence of drought events by using different correlations. Penalba and Rivera () studied the ENSO influences on SPI (3 and 12 months) for Southern South America by using principal component analysis in seven climatically and geographically homogenous regions. In their study they identified for all regions signals of El Niño (wet conditions) and La Niña (dry conditions) in the SPI indices, being more consistent during El Niño events.…”
Section: Introductionmentioning
confidence: 99%